2008
DOI: 10.4103/0970-0358.39666
|View full text |Cite
|
Sign up to set email alerts
|

Perineal burn contractures: An experience in tertiary hospital of a Himalayan state

Abstract: Perineal burn contracture is a rare burn sequel. We conducted a retrospective analysis of cases with perineal burn contractures managed in a tertiary care centre of a Himalayan state. We found that all cases sustained burn injury from burning firewood and the time of presentation was two to six years after the burn injury. We analyzed our treatment method and have classified these contractures into two types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…This is probably one of the few case reports of a patient with such severe post burn deformity of the perineum and the lower abdomen to the degree that the clitoris, and the labias anterior 2/3 almost invisible, presenting in the third trimester of her pregnancy due to childhood burns. Post burn contracture of the perineum is a rare burn sequel and the present case report is a secondary perineal burn contracture[ 1 ] with burns not involving the perineum directly but causing obliteration of the perineum by forming scar bands across the external genitalia. The mean age of patients at time of burns in such cases is 7.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably one of the few case reports of a patient with such severe post burn deformity of the perineum and the lower abdomen to the degree that the clitoris, and the labias anterior 2/3 almost invisible, presenting in the third trimester of her pregnancy due to childhood burns. Post burn contracture of the perineum is a rare burn sequel and the present case report is a secondary perineal burn contracture[ 1 ] with burns not involving the perineum directly but causing obliteration of the perineum by forming scar bands across the external genitalia. The mean age of patients at time of burns in such cases is 7.…”
Section: Discussionmentioning
confidence: 99%
“…Abdel-Razek [ 1 ] reported accidental chemical (sulphuric acid) burns to the genitalia. Thakur et al [ 2 ] reported perineal burns caused by fire wood used in open “chullah.” In our series burns to the groin and perineum were mostly due to “Kangri” use (77.56%), open “chullah” (8.16%), hot water (8.16%), and flames (6.12%).…”
Section: Discussionmentioning
confidence: 99%
“…Child abuse is also a risk factor in perineal and genital burns [ 8 ]. “Chullah,” an earthen made stove in which wood is used as fuel in the rural areas of India, is important cause for the perineal burns [ 2 ]. Use of loose clothes during cooking, spilling of kerosene on the clothes from a burning stove, or explosion of such stoves are also associated with perineal and genital burns [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Early excision of burns of the penile shaft and repair with a preputial flap or mesh split skin graft produces excellent results, with a reduction in complications. [2] Educating people for early medical consultation and proper postoperative care and rehabilitation can prevent these burn sequelae.…”
mentioning
confidence: 99%